The effect of the order-disorder transition on the electrical, magnetic and mechanical properties of Vicalloy I. (February 2017) - Hasani, S.; Shafyei, A.; Nezakat, M.; Mostaan, H.; Behjati, P.; Sahu, P.
Abstract: In this study, occurrence of ordering transition of FeCo-7.15 V alloy was investigated by evolutions of electrical resistivity during annealing process. Maximum and minimum resistivities were achieved when the alloy was annealed at ∼400 °C, and ∼600 °C, respectively. Characterization techniques including transmission electron microscopy and X-ray diffraction revealed that ordering transition occurs during various stages and critical ordering transition temperature as a particularly important temperature was obtained. It was also found that the extremum resistivities are related to formation of maximum short range ordered phase and long range order phase. In addition, the magnetic measurements by vibrating sample magnetometer showed that formation of anti-phase boundaries leads to a raise in coercivity by annealing at 550–650 °C. In the same way, hardness of the alloy was increased by annealing at this temperature range. But, on the other hand, the ordered alloy exhibited brittle behavior due to the dissociation of unit dislocations into partial dislocations. Graphical abstract: Highlights: A study on the ordering transition by TEM in Vicalloy I. The effect of short range and long range order on the resistivity of Vicalloy I. The effect of ordering transition on the magnetic and mechanical properties. The effect of vanadium-rich precipitation formation on the magnetic properties.